Key Factors Influencing on Implementation of Integrated Management of Childhood Illness (IMCI): A Systematic Review - Pinto, Joaquim; Wahyuningsih, Sayekti; Sentot, Imam; Peristiowati, Yuly; Puspitasari, Yenny; Anggraini, Novita Ana (Disease and Health Research: New Insights Vol. 5, 2024)
Background: The Integrated Management of Childhood Illness (IMCI) is a strategy that was developed by the World Health Organization (WHO) and the United Nations International Children’s Fund (UNICEF) in 1992 as an integrated approach to improve child health. IMCI is needed to address infant mortality in sub-Saharan African and South Asian countries of 11 million cases, due to diarrheal diseases, pneumonia, measles, malnutrition and newborn care problems. IMCI is an approach to managing sick children carried out integrated by combining promotion, prevention, and treatment services for the five leading causes of death in infants and children in developing countries. IMCI is used as a service standard for sick infants and childhood illnesses and a guideline for health workers, especially nurses and midwives and doctors in primary healthcare facilities. IMCI contributes significantly to reducing the mortality rate of neonates, infants and children if implemented widely, properly, and correctly. Purpose: The primary purpose of the study is to determine the key factors impacting the implementation on integrated management of childhood illnesses (IMCI). Methods: The design of this study uses systematic review, namely literature research that assesses critically quality health journals, which have been filtered with inclusion criteria and used several Google Scholar, Science Direct and Research Gate databases as literacy in this study. This systematic review is limited to a literature search in the last 10 years (2012- 2022) by using the following keywords: IMCI, Factors, determinant, Perception, Implementation "integrated management of childhood illnesses". There were 215 results according to the keywords Impact, implementation IMCI, and perceptions. Results: One of the factors hindering the implementation of IMCI is the national and regional strategies that do not provide space for stakeholders to review, monitor and evaluate the program. The factors that cause to implementation of IMCI are supervised by the head of community health, district authority, attitude of health workers, logistics support, experience, knowledge, and perception of health staff trained on IMCI determine in process application in each health facility. Conclusion: Leadership, logistic support, monitoring and supervision and coordination have an impact on the IMCI implementation process.